Pengaruh Struktur Modal Terhadap Profitabilitas (Studi Pada Perusahaan Pertambangan Yang Terdaftar di Bursa Efek Indonesia Periode 2011-2015) - Fauzan, Mitha Rahma; Mukaram (Jurnal Riset Bisnis dan Investasi, 2017)
Capital structure is one of the issue that attract many researchers in the field of finance and an important issue for any company because of its capability to directly effect on companies’ financial position. This study aims to determine the effect of debt to equity ratio (DER) and debt to assets ratio (DAR) as the dimension of capital structure to return on equity (ROE) and return on assets (ROA) as dimensions of company profitability ratios, either simultaneously or partially on mining companies listed in Indonesia Stock Exchange period 2011-2015. This research was conducted by using multiple linear regression analysis and yielded two equations of regression model. The data obtained are secondary data using documentation method. The result of regression analysis shows that the two dimensions of capital structure have significant effect to both dimensions of profitability simultaneously. While partially, only DAR which have a significant effect on the ROE and ROA.